Does an educated mind take the broader view? A field experiment on in-group favouritism among microcredit clients - Ivar Kolstad; Arne Wiig (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
A number of studies document an in-group bias in social dilemma situations. While group structure and dynamics are important in shaping in-group favouritism, less attention has been paid to individual characteristics affecting favouritism. Using data from dictator games conducted among 523 microcredit clients in Angola, this paper analyzes the effect of education on in-group favouritism. When addressing the endogeneity of education, we find that education increases in-group bias. This goes against the conventional view that education broadens the perspectives of an individual. In addition, our results suggest that in-group favouritism is related to gender, family background and access to particular forms of networks.
Keywords: C72; C93; D03; O12; 330; in-group favouritism; parochialism; field experiment; social preferences; microcredit